Analisis Potensi Bahaya Dan Resiko Dengan Menggunakan Job Safety Analisis di Rumah Sakit - Frico Talumewo; Diana Van Doda; Aaltje Ellen Manampiring (Indonesian Journal of Public Health and Community Medicine, 2020)
Siloam Hospitals Manado, apart from being a health facility, is also a workplace that has potential hazards and risks. The purpose of this study was to identify the potential hazards and the level of risk in the emergency room of Siloam Hospital Manado and to develop recommendations for controlling these risks. This research method is descriptive qualitative with an observational approach using the Job Safety Analysis (JSA) method. The results of the study identified the potential hazards and risks in the emergency room of Siloam Hospital Manado, namely very high risk, bacterial and viral infections present in the patient's cough or droplet. High risk, viral or bacterial infection in body fluids or blood of patients infected through needles, IV needles, NGT, catheters, or during intubation and cardiopulmonary resuscitation. Moderate risk, patients who are angry at the officers, chest compressions during CPR, body posture during patient examining in a lower place, squatting position when put infusion or drug injection, moving the patient. Low risk, needle stick injury, slip on slippery floor, fall from stairs, chlorine powder irritation, drug liquid irritation, busy work schedule, radiation hazard. Control recommendations consist of substitution control, engineering, administration and use of Personal Protective Equipment (PPE).